2015
DOI: 10.1039/c4ra09147g
|View full text |Cite
|
Sign up to set email alerts
|

The optimization of thermoelectric properties in a PEDOT:PSS thin film through post-treatment

Abstract: Our study shows that by combination of co-solvent and temperature of solvent post treatment method, the highest power factor of 37.05 μW mK−2 is obtained for PEDOT:PSS post-treated with DMSO at 120 °C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
78
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 43 publications
4
78
0
Order By: Relevance
“…Aer the subsequent treatment with hydrazine, the s decreased from 2139 S cm À1 to 514 S cm À1 , while the S increased from 16.2 to 42.7 mV K À1 as the concentration of hydrazine increased from 0 to 2 wt%. This results in a best PF value of 93.5 mW K À2 m À1 , which is comparable to the PFs of some of PEDOT:PSS TE materials reported in the literature (Table S1 †) 24,29,[32][33][34][35][36] when the lm is treated with 0.15 wt% concentration of hydrazine.…”
Section: Resultssupporting
confidence: 82%
“…Aer the subsequent treatment with hydrazine, the s decreased from 2139 S cm À1 to 514 S cm À1 , while the S increased from 16.2 to 42.7 mV K À1 as the concentration of hydrazine increased from 0 to 2 wt%. This results in a best PF value of 93.5 mW K À2 m À1 , which is comparable to the PFs of some of PEDOT:PSS TE materials reported in the literature (Table S1 †) 24,29,[32][33][34][35][36] when the lm is treated with 0.15 wt% concentration of hydrazine.…”
Section: Resultssupporting
confidence: 82%
“…All these recent significant breakthroughs in the TE performances of PEDOT came from the optimization method by controlling the oxidation level, which suggested that this technique was effective and promising. On the other hand, in a newly-published literature, Liu et al [29] systematically investigated the effect of co-solvents consisting of DMSO and EG on the TE performances of PEDOT:PSS films. In fact, as previously reported, [29][30][31][32][33] co-solvents system has been confirmed to exhibit synergistic effect on physical properties of materials such as solubility, adsorption, micellar, liquefaction and electrical conductivity etc.…”
Section: Introductionmentioning
confidence: 98%
“…Mixed solutions have been shown to exhibit several unique advantages, because of the formation of hydrogen bonds, variation of the binding energy, and the regulation of dielectric constant. Furthermore, mixed solutions can display a synergetic influence on the performance of materials . Thus, the introduction of mixed solvents during post‐treatment is a promising and useful approach.…”
Section: Introductionmentioning
confidence: 99%